(untitled) (Annals of Medical Research, 2021)
Aim: Transdiscal-transcrural celiac plexus block is one of the most effective treatments for chronic upper abdominal pain. This study was done to show that simulated computed tomography (CT) measurements of celiac plexus block may be able to facilitate the practitioner during the procedure.Material and Methods: Thin-section abdomino-pelvic CT images of 100 patients (50 females, 50 males) were retrospectively reviewed. Using special software, the transdiscal-transcrural celiac plexus block was simulated to measure the optimal distance of needle entry from the midline, as well as the optimal needle entry angle and needle tip penetration depth.Results: The optimal needle entry distance from the midline was 4.06 ± 0.66 cm for the right side (RM) and 4.08±0.65 cm for the left side (LM). The mean optimal needle entry angle was 20.17±2.86º on the right side and 20.5±2.33º on the left. The mean optimal needle penetration depth was 11.78±1.22 cm on the right and 11.72±1.18 cm on the left side. No abdominal solid organ penetration was observed on the path of needle advancement.Conclusion: In this study, simulated transdiscal-transcrural celiac plexus block parameters on CT provided guidance to those who performed the procedure. In addition, the absence of any abdominal solid organ penetration in the simulated virtual needle traces supports the hypothesis that the technique has a very low risk of complications.Keywords: Celiac plexus block; computed tomography; transdiscal, sympathetic ganglion block.